The innkeeper of ivy hill eaudiobook Tales from ivy hill series, book 1. - Klassen, Julie (Tales from Ivy Hill, 2016)
The lifeblood of the Wiltshire village of Ivy Hill is its coaching inn, The Bell. But when the innkeeper dies suddenly, his genteel wife, Jane Bell, becomes the reluctant owner. Jane has no notion of how to run a business. However, with the town's livelihood at stake and a large loan due, she must find a way to bring new life to the inn. Despite their strained relationship, Jane turns to her resentful mother-in-law, Thora, for help. Formerly mistress of The Bell, Thora is struggling to find her place in the world. As she and Jane work together, they form a measure of trust, and Thora's wounded heart begins to heal. When she encounters two men from her past, she sees them—and her future—in a different light. With pressure mounting from the bank, Jane employs innovative methods to turn the inn around, and puzzles over the intentions of several men who seem to have a vested interest in the place. Will her efforts be enough to save The Bell? And will Thora embrace the possibility of a second chance at love?